Factors influencing child workers' migration from Lao PDR to Thailand and its consequences : a case study of child domestic workers - Syvongsay Changpitikoun; Supang Chantavanich (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2008